2013
DOI: 10.5194/se-4-179-2013
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of laterally variable subductions: laboratory models applied to the Hellenides

Abstract: Abstract. We designed three-dimensional dynamically selfconsistent laboratory models of subduction to analyse the relationships between overriding plate deformation and subduction dynamics in the upper mantle. We investigated the effects of the subduction of a lithosphere of laterally variable buoyancy on the temporal evolution of trench kinematics and shape, horizontal flow at the top of the asthenosphere, dynamic topography and deformation of the overriding plate. Two subducting units, which correspond to a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 91 publications
(129 reference statements)
1
47
1
Order By: Relevance
“…Since the end of the Eocene (30-35 Ma), slab retreat has induced the formation of back-arc basins and the mountain belts formed earlier have collapsed, forming the Alboran Sea, the Ligurian-Provençal basin, the Tyrrhenian Sea, the Pannonian Basin and the Aegean Sea (Le Pichon and Angelier, 1981;Malinverno and Ryan, 1986;Royden, 1993;Wortel and Spakman, 2000;Jolivet and Faccenna, 2000;Faccenna et al, 2003;Jolivet and Brun, 2010;Guillaume et al, 2013).…”
Section: Geodynamic Of the Aegean Seamentioning
confidence: 99%
“…Since the end of the Eocene (30-35 Ma), slab retreat has induced the formation of back-arc basins and the mountain belts formed earlier have collapsed, forming the Alboran Sea, the Ligurian-Provençal basin, the Tyrrhenian Sea, the Pannonian Basin and the Aegean Sea (Le Pichon and Angelier, 1981;Malinverno and Ryan, 1986;Royden, 1993;Wortel and Spakman, 2000;Jolivet and Faccenna, 2000;Faccenna et al, 2003;Jolivet and Brun, 2010;Guillaume et al, 2013).…”
Section: Geodynamic Of the Aegean Seamentioning
confidence: 99%
“…Alboran Sea, Liguro-Provençal Basin, Tyrrhenian Sea, Aegean Sea, Pannonian Basin) results from slab backward migration and their tearing or break-off (Wortel and Spakman, 2000;Faccenna et al, 2004;Papanikolaou and Royden, 2007;Royden and Papanikolaou, 2011;Berk Biryol et al, 2011;van Hinsbergen and Schmid, 2012;Jolivet et al, 2013;Guillaume et al, 2013;Gessner et al, 2013;Schildgen et al, 2014). The progressive tearing of the Tyrrhenian slab has resulted in the present steeply-dipping narrow stripe of lithosphere seen in tomographic models and in a progressive acceleration of slab retreat with time (Carminati et al, 1998;Faccenna et al, 2004;Rosenbaum and Lister, 2004;Faccenna et al, 2007).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In a more recent study, Sternai et al (2014) model the distribution of strain in the upper plate above a slab tear but the detailed kinematics of exhumed material above the tear is not modelled either. By mean of analogue modelling Guillaume et al (2013) have explored the effect of lateral variations in the nature of the subducting plate (oceanic vs continental) and they suggested that the western recent tear of the Aegean slab is responsible for the dextral shearing of the upper plate and formation of the Central Hellenic Shear Zone described by Royden and Papanikolaou (2011). Piromallo and Morelli (2003).…”
Section: Who Have Interpreted the Exhumation And Extension Of The Menmentioning
confidence: 99%
“…By adding fine iron powder (Funiciello et al, 2004;Schellart, 2008; sample h R σ r Newtonian Power-law rs Figure 3: Schematic rheometer setup, with gap height h and disk radius R, including a schematic depiction of shear stress σ variation as function of radial distance r for Newtonian and power-law materials, rs is the radial distance where the shear stress curves of Newtonian as well as power-law materials intersect (Carvalho et al, 1994). Guillaume et al, 2013) we adjust the mixture density to be able to create both buoyant and negatively buoyant materials. We mix and homogenise materials by hand.…”
Section: Iron Powdermentioning
confidence: 99%
“…Guillaume et al (2013) present a model that includes subduction of continental lithosphere, where the model is driven by buoyancy only and Newtonian viscous materials are applied. However, no break-off occurs after continental material has subducted.…”
Section: Materials Application: Slab Break-offmentioning
confidence: 99%